Effect of Placental Cord Drainage on the Duration of Third Stage of Labor (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the effect of placental cord drainage on the duration of third stage of labor, and to assess the safety of this method regarding risk of postpartum hemorrhage, retained placenta, incidence of manual removal of placenta, and the need for blood transfusion.Material and Method: A randomized controlled trial was carried out in gynae unit 4 of SGRH/ FJMC Lahore on 200 pregnant women. Out of these 100 cases were assigned to the study group and 100 cases to the control group. In the study group, placental cord drainage was performed. In both groups, the placenta was delivered by brandt Andrew method and inj oxytocin 10 units was given I/v at delivery of anterior shoulder. The duration of third stage was compared as the primary outcome. The incidence of postpartum hemorrhage, retained placenta, manual removal of placenta, and the need for blood transfusion were also compared between the two groups. Data was recorded on a Performa and t-test was used for statistical analysis.Results: The average duration of third stage of labor was 5.02 ± 1.71minutes in the study group and 7.42 ± 2.56 minutes in the control group. This difference was highly significant (P< 0,001). The average blood loss during third stage was noted to be 175.05±118.15 ml in the study group and 252.05±145.48 mL in the control group, which was significantly high (P
Keywords: Placental cord drainage, Third stage labour, Retained placenta, Postpartum hemorrhage